2020
DOI: 10.32615/bp.2020.006
|View full text |Cite
|
Sign up to set email alerts
|

Induction of somatic embryogenesis and evaluation of genetic stability in regenerated plants of Magnolia dealbata

Abstract: The utility of plant tissue culture for the mass propagation of trees is well known, but continuous in vitro multiplication of plant material may increase the possibility of somaclonal variation; therefore, it is essential to evaluate the genetic integrity of regenerants from species-specific in vitro protocols prior to mass production and implementation. The objectives of this study were: 1) to determine the effect of 2,4-dichlorophenoxyacetic acid (2,4-D) concentration over two cycles of secondary somatic em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Our results showed that the secondary embryo formation occurred at low efficiency on hormone-free medium or medium containing only 2,4-D. In Tetrapleura tetraptera [ 58 ] and M. dealbata [ 49 ], secondary se were formed on the media supplemented with 2,4-D only.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our results showed that the secondary embryo formation occurred at low efficiency on hormone-free medium or medium containing only 2,4-D. In Tetrapleura tetraptera [ 58 ] and M. dealbata [ 49 ], secondary se were formed on the media supplemented with 2,4-D only.…”
Section: Discussionmentioning
confidence: 82%
“…Namely, 2,4-D and CPPU successfully induced both primary [ 13 ] and secondary SE in C. erythraea ( Figure 2 , Figure 3 , Figure 4 and Figure 5 ). Similarly, 2,4-D induced both primary and secondary SE in peanut [ 48 ] and Magnolia dealbata [ 49 ], while in some species, hormone-free medium was suitable for efficient induction of both primary and secondary SE [ 33 ]. However, there are cases where primary SE is induced by PGRs, but the induction of the secondary SE requires a medium without PGRs for its completion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean similarity among the analyzed genotypes was 0.90, which indicated rather minor changes within the studied group of regenerants. The level of polymorphism in the range of 10–15% indicates low genetic variability for the SSR, RAPD and ISSR markers [ 35 , 36 , 38 ]. Etminan et al [ 39 ] and Shahlaei et al [ 40 ] reported that the verification of the results with SCoT markers could lead to different conclusions due to the higher informativeness of this marker compared to other marker systems.…”
Section: Resultsmentioning
confidence: 99%